TRADITIONAL AND CULTURAL TOURISM OBJECTS OF RAJA PRAILIU VILLAGE IN THE CRISIS OF THE NEW NORMALITY ERA - Gunawan, Fransiskus Xaverius Candra (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The dynamics of tourism development that is so rapid has caused disruption to the existence of the community life order in the Prailiu traditional village tourist attraction in East Sumba Regency. On the one hand, this has a positive impact on economic growth on a macro scale. On the other hand, it has the risk of threatening the sustainability of the micro economy and culture. Therefore, the purpose of this study is to analyze the extent of the readiness and needs of the community to enter the world of tourism, especially ikat weaving craftsmen. In addition, this study is also part of the education process related to the importance of implementing community-based tourism. The research method uses a qualitative descriptive approach based on secondary and primary data obtained through observation, documentation and in-depth interviews. The analysis technique uses the SWOT quadrant matrix analysis approach. The results of the study found the reality that ikat weaving craftsmen experienced serious pressure on business sustainability. In addition, threats to the preservation of culture and local wisdom need special attention to avoid the death of the local community's economy. The implications of this study state that the application of the concept of community-based tourism should be a strategy implemented by the Regional Government to increase local economic empowerment and at the same time maintain the existence of the Raja Prailiu village culture in the vortex of new normal changes that require strong adaptability to survive. Keywords: community-based tourism, sustainable development, ikat weaving craftsmen, Raja Prailiu village, new normality.